Effects of Varying Reverberation on Music Perception for Young Normal-Hearing and Old Hearing-Impaired Listeners. (January 2018) - Reinhart, Paul N.; Souza, Pamela E.
Reverberation enhances music perception and is one of the most important acoustic factors in auditorium design. However, previous research on reverberant music perception has focused on young normal-hearing (YNH) listeners. Old hearing-impaired (OHI) listeners have degraded spatial auditory processing; therefore, they may perceive reverberant music differently. Two experiments were conducted examining the effects of varying reverberation on music perception for YNH and OHI listeners. Experiment 1 examined whether YNH listeners and OHI listeners prefer different amounts of reverberation for classical music listening. Symphonic excerpts were processed at a range of reverberation times using a point-source simulation. Listeners performed a paired-comparisons task in which they heard two excerpts with different reverberation times, and they indicated which they preferred. The YNH group preferred a reverberation time of 2.5 s; however, the OHI group did not demonstrate any significant preference. Experiment 2 examined whether OHI listeners are less sensitive to (e, less able to discriminate) differences in reverberation time than YNH listeners. YNH and OHI participants listened to pairs of music excerpts and indicated whether they perceived the same or different amount of reverberation. Results indicated that the ability of both groups to detect differences in reverberation time improved with increasing reverberation time difference. However, discrimination was poorer for the OHI group than for the YNH group. This suggests that OHI listeners are less sensitive to differences in reverberation when listening to music than YNH listeners, which might explain the lack of group reverberation time preferences of the OHI group.